Peran Hara N, P dan K pada Pertumbuhan dan Perkembangan Ratun Lima Genotipe Padi - , Susilawati; Bambang Sapta Purwoko; Hajrial Aswidinnoor; Edi Santosa (Indonesian Journal of Agronomy, 2012)
The objective of the research was to determine the roles of fertilizers application in improving rice ratoons. Statistical design used was a factorial randomized complete block design with three replications. The first factor was three levels of fertilizer rate (kg ha-1) i.e. 5 N + 27 P2O5; 45 N + 30 K2O; and 27 P2O5+30 K2O. The second factor was rice genotypes, i.e. Cimelati, Hipa-5 and Rokan varieties, and two lines of rice i.e. IPB106-7-47-DJ-1 and IPB106-F-8-1. The growth and production characters of main crops and ratoon were observed. The results showed that both genotypes and rates of fertilizer affected yield of ratoon. Following application of (kg ha-1) 45 N + 27 P2O5 three genotypes produced the highest ratoon, i.e. IPB106-7-47-DJ-1 and IPB106-F-8-1 lines and Rokan variety. Cimelati and Hipa-5 varieties produced higher number of ratoon with fertilizer rate (kg ha-1) 45 N + 30 K2O. Ratoon production of all genotypes ranged 38.1-56.6% of the main crop. This study clearly demonstrated that N, P and K fertilizer had important roles in increasing yield and yield components of rice ratoon. Keywords: fertilizer, productivity, rice genotypes, rice ratoon